Harmonic distortion analysis in power system due to geomagnetically induced currents - Khurshid, Z.M.; Ab Kadir, M. Z. A.; Ab Aziz, N. F.; Rhazali, Z.A.; Azis, N. (Elsevier, 2025)
Geomagnetically induced currents (GICs) flowing through power transformers during geomagnetic disturbances (GMD) can cause increased reactive power demands, voltage stability issues, and significant harmonic distortions in the system due to transformer half-cycle saturation. The harmonic contents in transformers vary based on core type, air-path flux, and transformer configuration. These effects ultimately impact the quality and reliability of power transfers in the system. This paper investigates the harmonic distortions of a small-scale system with different types of transformers in the Malaysian power grid under GIC events. The simulation model is built using Power Systems Computer-Aided Design (PSCAD) software, and simulation results are computed for various GIC values. The results show that transformer saturation due to GICs can generate high levels of harmonics in the system and drastically increase reactive power losses. The worst-case harmonics are observed in the current waveforms through the static VAr compensator (SVC) connected to a 500 kV bus. Based on the findings, recommendations are provided to the industry and system operators to mitigate the harmonics and their effects during GMD events.